车用液压机械复合传动特性及应用研究 - 杜玖玉; 苑士华; 郭占正 (Jixie chuandong)
Hydro-mechanical transmission integrates the benefits of hydrostatic and the mechanical transmission,including variable speed ratio,high transmission efficiency,improved power capacity and extended speed ratio range. The characteristics of two kinds of Hydro-mechanical transmission are analyzed and the respecting applying also are provided. The shortcoming of the existing HMT style is provided as well with the advice.